1998
DOI: 10.1111/j.1447-0756.1998.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Antenatal Risk Coding and the Outcome of Pregnancy

Abstract: The coding system is ineffective with Malaysia's relatively low reproductive risk. Women require more personalised counseling about risk to make appropriate choices. Better results depend on simpler but consistent selection for hospital delivery using reproductive history, combined with better communication and transport systems for home deliveries and a reorientation within hospitals to rapid emergency care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Low effectiveness of antenatal risk assessment has also been observed in other countries and many risk factors have shown to be poor predictors of adverse outcomes ( Maine 1991; McDonagh 1996; Geefhuysen et al . 1998 ; Jahn et al .…”
Section: Discussionmentioning
confidence: 99%
“…Low effectiveness of antenatal risk assessment has also been observed in other countries and many risk factors have shown to be poor predictors of adverse outcomes ( Maine 1991; McDonagh 1996; Geefhuysen et al . 1998 ; Jahn et al .…”
Section: Discussionmentioning
confidence: 99%
“…In urban Guinea-Bissau, 20 of 125 acutely ill children died either on their way to hospital or while waiting in the reception area of an outpatient clinic [6]. In Malaysia, a team assessing the value of the risk-coding system in pregnancy concluded that better communications, a more effective transport system, and better emergency care in hospitals were needed in order to reduce maternal mortality [7]. This represents empirical evidence providing emergency transport saves lives.…”
Section: Introductionmentioning
confidence: 99%
“…In Guinea-Bissau, 20 of 125 acutely ill children died either on their way to hospital or while waiting in the reception area of an outpatient clinic [5]. In Malaysia, a team assessing the value of the risk coding system in pregnancy concluded that better communications, a more effective transport system, and better emergency care in hospitals were needed in order to reduce maternal mortality [6]. Karachi is a city with a population of 16 million.…”
Section: Introductionmentioning
confidence: 99%